In-Between Mobile Maps and Media: Movement. (May 2017) - Wilmott, Clancy
This article moves beyond the textuality of the map to focus on the way in which mobile mapping is constructed discursively, semiotically, and experientially. It centers on the autoethnographic and reflective experience of the researcher analyzing video and Global Positioning System (GPS) recordings of walking interviews, during which the interviewees conversed about, and engaged in, mobile mapping practices. This reductive process can be considered in light of its re-presentation to the researcher for analytical purposes—a ghostly abstraction of a past spatial experience. The article considers the manifold hauntings stirred in the process of abstraction and the creation of multiple layers of experience: that of the firsthand experience of the walking interview and that of the secondhand analysis of the video and geocoded data. The discrepancy between firsthand movement and secondhand analysis underscores questions about the relationship between mobile maps, representation, and movement and about those epistemologies and ontologies that haunt the interstices between individual records.